Promoting African Languages and Culture through Service Learning in the USA - Maganda, Dainess M. (Advances in Social Sciences Research Journal, 2018)
This study shows the relevance and prominence of Swahili language and culture in America. It underscores the nature, presence and relevance of African languages in America. Through Service learning approach, Swahili students, guided by their teachers offered Swahili language and culture lessons to the elderly in one of the counties in Georgia for 6 weeks. Data seem to suggest that the elderly were surprised at the presence of Swahili in their first language and its prominence in American social media; they appreciated various aspects of African culture, namely- Africans’ respect of the elderly, greeting one another, and the versatile nature of African clothes. The elderly showed great interest in learning more about Swahili language and culture. The author calls on other Africanists to find ways to educate the American public about African languages and culture. Teaching implications include the need for teachers to be intentional and strategic about finding ways to use language and culture courses as panacea for promoting minority languages and cultures around the world.